A case of near-hanging (Indian Journal of Case Reports, 2019)
Hanging is the suspension of a person by a noose or ligature around the neck and has been a common method of capital punishment since medieval times. Hanging is also a common method of suicide/homicide worldwide as also in India. We report a case of attempted suicidal hanging admitted in our intensive care unit. The patient, a 32-year old male, presented with poor clinical status, in gasping condition, hypoxemic and required immediate intubation, resuscitation, assisted ventilation and intensive care treatment. He received standard supportive intensive care and made a full clinical recovery without any neurological deficit. The purpose of the case report is to emphasize that the cases of near-hanging need to be aggressively resuscitated and managed irrespective of dismal initial presentation.